Comparison of Genital Chlamydia trachomatis Infection Incidence Between Women With Infertility and Healthy Women in Iran Using PCR and Immunofluorescence Methods - Marashi, Seyed Mahmoud Amin (Kowsar, 2014)
BACKGROUND: For a long time, infertility has been one of the most sequels in medical sciences with microbial agents as one group of its causes. The possible etiological role of Chlamydia trachomatis in infertility was suggested years ago, but it has not yet been proved completely. To decrease the severe involvements of C. trachomatis infections, screening by efficient diagnostic methods are necessary. OBJECTIVES: In this study we attempted to determine the incidence of C. trachomatis in infertile women and compared this with healthy women. MATERIALS AND METHODS: This case-control study was performed on 150 infertile women with unknown causes and without physiological deficiency for infertility. The control group consisted of 200 fertile safe and impregnated women. Presence of C. trachomatis in the two groups was examined by direct and indirect immunofluorescence tests and PCR. RESULTS: C. trachomatis was detected by direct immunofluorescence method in 23 (15.3%) infertile women compared and 7 (3.5%) healthy controls. Using indirect immunofluorescence tests, a positive test titer of 1:16 as well as the above results were detected in 34 (22.6%) of the infertile cases and 9 (4.5%) of the controls. C. trachomatis was detected by PCR method in 48 (32%) infertile women and 13 (8.7%) among the controls. CONCLUSIONS: The results of our study suggest that there is a significant association between C. trachomatis infection and female infertility.